Qualitative investigation of sensitive topics in tax compliance study in Malaysia - Mohdali, Raihana; Wan Zakaria, Wan Normeza; Mohd. Ali, Nor Adura; Abdul Salam, Zarina (Human Resource Management Academic Research Society (HRMARS), 2019)
Most researchers would probably agree on subject matters that possess sensitive elements such as income, sex, religion and politics. These topics are believed to be relatively intrusive and inappropriate to some. The same goes to issues related to tax compliance and other pressing matters surrounding it. Thus, the purpose of this research is to probe areas related to tax compliance study that can be considered as sensitive. Depth interview was employed for this qualitative study to collect data. The interviews were conducted with 14 taxpayers from various age groups and social backgrounds. The findings were analysed based on the verbal responses recorded and transcribed from all participants in verbatim. Issues related to government and religions have resulted in intensed reactions by the respondents more so than other topics. This is evident in the verbal responses, physical reactions and emotions portrayed by the participants. There are two main constraints in the study which are the different race and religious faith between the researcher and participants and the small number of the subjects involved in this study. Topics related to government issues are seen to top the list in causing the most extreme reaction in respondents followed by questions on the role of religious values. Questions on other areas do not trigger much stir.